Economic and strategic analysis of scientific journals: recent evolutions - Savenije, Bas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Almost 75% of the current academic journals have gone online, even as they continue to be published in print. Furthermore, a rising number of new e-only journals are being started, most of them outside the range of traditional publishers. It is an interesting issue how these developments have influenced the policy of traditional publishers. This paper describes and analyses recent developments in traditional commercial scientific journal publishing, taking into account important aspects such as pricing policy, mergers and acquisitions, licensing variants, and attitudes towards open access. The trends that can be observed give some insight into possible future scenarios and their probability.